GenderUp(date): Progress towards outcomes - Gregerson, Katheryn; Kilwinger, Fleur; Schut, Marc; McGuire, Erin; Rietveld, Anne; Leeuwis, C. (CGIAR, 2023)
In this report progress report we reflect upon impact of GenderUp in the AR4D space, including its application across various scaling teams, discussions it has evoked, and its influence on other scaling tools. We describe different updates that are meant to give interested innovation teams a better understanding of. • The GenderUp process and insights that innovation teams have obtained through GenderUp. • Improvements to the GenderUp method and website in response to its actual application. • How elements of GenderUp are currently being institutionalized in the CGIAR. • Research spinoffs inspired by GenderUp.